(untitled) (American Journal of Geospatial Technology, 2023)
The study attempted to identify the groundwater potential zones in Birnin Kudu Local Government Area of Jigawa State, Nigeria using Remote Sensing and Geographic Information System techniques. Groundwater is an important source for water supply, considering its availability, quality, cost and time effective to develop, and simple accessibility. The study used thematic maps like Rainfall, Lineament, Geology, Soil, DEM Soil, Drainage and Land Use Land Cover map as GIS layers in geo-database. The rankings/weights of factor contributing to groundwater prospects in the study area were evaluated by pair wise comparison using Analytical Hierarchy Process (AHP). Weightages of the factors influencing groundwater prospects zones in the study area shows that rainfall is one of the major contributor, and was weighed as the highest contributor with (34%) followed by lineament (24%) and geology was weighed (14%). The least groundwater contributor in the study area is the land use land cover with (2%). The study showed that the very high groundwater potential areas occupy 59.92 km2 (2.89%) of the area, the high potential zones constitute about 527.52km2 (25.45%) of the study area and the moderate potential area has the highest area of 602.69km2 (29.07%). The low and very low potentials occupy an area of about 528.13 km2 (25.48%) and 354.75 km2 (17.11%) respectively. The study concluded that the study area has an abundance.